Teaching to Display Text, Symbols, and ASCII Images Using Turbo Pascal to First-Semester Electrical Engineering Students - Ulul Ilmi; Mochammad Sholikhin (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
This community service activity aims to help first-semester Electrical Engineering students improve their understanding of basic programming concepts using Turbo Pascal, with a focus on displaying text, symbols, and ASCII-based images. The approach combines both theoretical instruction and hands-on practice. Students receive materials covering the use of the Write and Writeln functions in Turbo Pascal, as well as techniques for creating simple text-based images using ASCII characters. The results show that most students have successfully grasped the material, created basic programs, and actively participated in the training sessions. This activity is designed to strengthen the programming foundation of Electrical Engineering students, providing a solid base for further development of their programming skills.